Analysis of Factors Affecting Wages of Female Workers in Manufacturing Industries - Insaad, Thitawan; Kosalakorn Permpoonwiwat , Chompoonuh; Kulkolkarn, Kiriya (King Prajadhipok’s Institute Journal, 2022)
This study investigated the trends concerning female workers’ wages and analyzed the factors that influenced the wages of female workers in large, medium, and small production industries. The study drew on data collected by the National Statistical Office in its Labor Force Survey (LFS) done in third quarter for the years 2010 to 2019. This study showed that education was a significant variable in female workers’ wages. The higher the education level, the better pay that female workers would receive. It was found that family childcare-related characteristics had the opposite impact on wages. The female laborers carried the burden of handling both housework and their careers. Female workers should obtain appropriate wages compared to their burdens to make end meets and covers all expenses. Therefore, the government sector needs to invest more in education and seriously promote lifelong learning to develop the workers’ competencies. This will provide better opportunities for female workers to gain more wages. The government should also point out the importance of female workers in private companies by developing better social welfare and benefits of child care for female workers in the workplace.